Lecturers’ Perception in Integrating ICC Components in Teaching English as Foreign Language at University Level - Akhmad, Enni; Basalama, Nonny; Otoluwa, Moon Hidayati; Dako, Rahman Taufiqrianto; Mahmud, Karmila; Ibrahim, Syahrun (International Journal of Scientific Research and Management (IJSRM), 2024)
This article aims to explore the lecturers’ perception in integrating ICC in teaching English as foreign language at university level. This research is conducted at Jurusan Tadris Bahasa Inggris, Fakultas Ilmu Tarbiyah dan Keguruan, IAIN Sultan Amai Gorontalo. The participants in this study are 2 lecturers who taught English Speaking Courses at Jurusan Tadris Bahasa Inggris, Fakultas Ilmu Tarbiyah dan Keguruan, IAIN Sultan Amai Gorontalo. This research used qualitative research methods with case study design. Data collection techniques used interview. Data analysis used thematic analysis. The results of the research shows three (3) findings, first, the perception of lecturers in integrating ICC Components occur based on three things, namely perceptions of the lecturers’ teaching experience, perceptions of multicultural society, and perception of students' language proficiency and motivation. This research implied to integrate ICC in teaching English as foreign language due to the role of ICC